2017
DOI: 10.1039/c7ra90096a
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Inhibition of mild steel corrosion in hydrochloric acid using two novel pyridine Schiff base derivatives: a comparative study of experimental and theoretical results

Abstract: Correction for ‘Inhibition of mild steel corrosion in hydrochloric acid using two novel pyridine Schiff base derivatives: a comparative study of experimental and theoretical results’ by Yue Meng et al., RSC Adv., 2017, 7, 43014–43029.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…As seen in Table 4, χ of the two corrosion inhibitor molecules obeys the following law: CTSB < HQ‐CTSB, which is consistent with the E LUMO trend. Typically, Δ N is a measurement of the electron transfer between the molecule and the metal 47 . When Δ N < 3.6, the contribution of electrons to the metal surface enhances the effectiveness of corrosion inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Table 4, χ of the two corrosion inhibitor molecules obeys the following law: CTSB < HQ‐CTSB, which is consistent with the E LUMO trend. Typically, Δ N is a measurement of the electron transfer between the molecule and the metal 47 . When Δ N < 3.6, the contribution of electrons to the metal surface enhances the effectiveness of corrosion inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, the prepared catalyst exhibits high efficiency and activity for photocatalytic oxidation of functionalized alcohol substrates under exposure to visible blue light (Scheme 1d). Many functionalized aromatic alcohol substrates including pyridinol compounds, which are important raw materials and widely used in pharmaceutical intermediates, pharmaceutical products, and pesticide chemicals, 35–39 are well tolerated under mild reaction conditions. Through characterization and result analysis, we confirmed that TiO 2 adsorption of benzyl alcohol to form surface complexes is the key to achieving visible light response, and the high specific surface area of TiO 2 is the key to achieving high catalytic activity.…”
Section: Introductionmentioning
confidence: 99%